2019
DOI: 10.1248/bpb.b19-00454
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Sleep Enhancement by Green Romaine Lettuce (<i>Lactuca sativa</i>) in a Rodent Model

Abstract: This study was conducted to investigate the effects of the extracts of green romaine lettuce (GRE) on sleep enhancement. GRE contains 1071.7 and 199.2 µg/g of extracts of lactucin and lactucopicrin, respectively, known as sleep enhancement substances. When 100 mg/kg of GRE was administered orally, sleep latency and duration time were significantly increased compared to controls (p < 0.05). Rapid eye movement (REM) sleep decreased with 100 mg/kg of GRE administration and non-REM (NREM) sleep also increased. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…In previous studies, the sleep-enhancing activity of green romaine lettuce, a type of Lactuca sativa , was confirmed in a rat model [ 13 ]. In the pentobarbital-induced sleep test, romaine lettuce leaf extract reduced sleep latency and increased sleep time.…”
Section: Introductionmentioning
confidence: 94%
“…In previous studies, the sleep-enhancing activity of green romaine lettuce, a type of Lactuca sativa , was confirmed in a rat model [ 13 ]. In the pentobarbital-induced sleep test, romaine lettuce leaf extract reduced sleep latency and increased sleep time.…”
Section: Introductionmentioning
confidence: 94%
“…The latexes were evaluated for lactucin-type guaianolides (lactucin, lactucopicrin, 11β,13-dihydrolactucin, and 11β,13-dihydrolactucopicrin), which are characteristic constituents of the Lactuca genus. According to the literature, these compounds have sedative effects, which have been shown in various studies and attempts have been made to prove this effect in both in vivo and in vitro experiments [4,15,16]. The constituents were separated using HPLC and quantified by a diode-array detector (DAD).…”
Section: Resultsmentioning
confidence: 99%
“…Sutrisna also reported significant analgesic, anti-inflammatory, antidepressant, and anti-coagulant properties and found that the 70% ethanolic extract of the leaves of L. sativa displayed a remarkable sedative effect [19]. Additionally, Kim et al showed that the 70% ethanolic extract of L. sativa enhanced sleeping time and acted via the GABAergic system [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations